A critical assessment of how local municipalities implement local economic development: case studies of Bergrivier and Cape Agulhas local municipalities - Modise, Keabetswe Charmyne (Department of Political Studies, 2026)
Local Economic Development (LED) has been instrumental in the restructuring and transformation of local government in South Africa's new democratic dispensation. LED facilitates the process through which municipalities could achieve the ‘developmental' role they acquired to tackle socio-economic issues such as unemployment, inequality, and poverty. Despite its prominence in various legislative and policy frameworks, municipalities in small towns and semi-rural areas face several challenges in implementing LED initiatives. This study presents a comparative analysis of LED implementation between Bergrivier Local Municipality and Cape Agulhas Local Municipality located in the Western Cape province. The study evaluated internal and external factors influencing the design and implementation of LED strategies. The comparison focused on institutional arrangements, intergovernmental relations, access to resources, and community engagement. Additionally, the research critically assessed the institutional capacity, political commitment and stakeholder involvement which shapes the roll out of LED strategies. Although both municipalities operated in accordance with the prevailing legislative frameworks governing LED, they differed noticeably in their governance structure, collaborative governance, and stakeholder engagement. As a result, the implementation modalities for LED varied, and were shaped by municipality's socio-economic circumstances, operational structure, and resource availability. Therefore, LM 1 has an LED unit with limited capacity, and primarily focus on coordination with national and provincial frameworks. The unit face obstacles with institutional and systemic barriers, resulting in a delicate cross-governmental collaboration, and ineffective participatory approach. This is further aggravated by growing unemployment rate and limited proficiency. On the other hand, LM 2 have a more targeted approach. The municipality benefits from its integrated LED and Tourism unit and pursues local initiatives such as SMME support and mentorship. Also, the municipality showed a more collaborative approach, integrating with the district municipality. Besides, the LM2 recently restructured its governance structure and anticipates improved approaches effectively implement LED strategies and create jobs. The study findings revealed that the intuitional capacity, stakeholder engagement and distribution of resources, plays a pivotal role in shaping the effectiveness of LED. The study suggests that both municipalities should refine their LED strategies with well-defined objectives, realistic financial plans, and sustainable LED principles. Each municipality has the potential to strengthen their institutional capacity, improve stakeholder engagement, and implement strong financial and monitoring frameworks, to ensure effective LED implementation.